Replacing egg yolk with soybean lecithin in the cryopreservation of stallion semen - Papa, Frederico Ozanam [UNESP]; Felicio, Gabriel Barcelos [UNESP]; Melo-Ona, Cely Marini [UNESP]; Alvarenga, Marco Antonio [UNESP]; De Vita, Bruna [UNESP]; Trinque, Cassio [UNESP]; Puoli-Filho, Jose Nicolau P. [UNESP]; Dell'aqua Junior, José Antônio [UNESP] (Elsevier B.V., 2011)
The objective of this study was to determine whether replacing the egg yolk with soybean lecithin in the Botu-Crio (R) cryodiluent would maintain the fertility of cryopreserved stallion sperm. Two experiments were performed to evaluate cell freezability. In experiment 1, sperm from 15 stallions were frozen in Botu-Crio (R) (BC) or Botu-Crio (R) which contained 45 g/L soybean lecithin (BCLS45) in place of the egg yolk. In experiment 2, we compared different concentrations of soybean lecithin: 0, 10.0, 12.5, 15.0, 17.5 and 20.0 g/L (BC, BCLS10, BCLS12.5, BCLS17.5 and BCLS20, respectively). In experiment 1, sperm frozen in BC and BCLS45 exhibited similar (P > 0.05) percentages of total motile sperm (61% and 61%, respectively); progressively motile sperm (27% and 27%, respectively) and sperm with intact plasma membranes (IMP; 53% and 57%, respectively). Similarly, sperm frozen in BC or BC containing any concentration of soybean lecithin maintained similar (P > 0.05) percentages of total motile sperm (61-68%) and progressively motile sperm (27-31%). In the first fertility trial, we used cryopreserved semen from a single stallion was inseminated into mares. The semen from the sperm that were frozen in BC diluent resulted in a higher fertility rate (66%, 16/24) compared to the sperm that were frozen in BCLS45 diluent (17%, 5/29; P < 0.01). Similarly, in a second fertility trial, the mares that were inseminated with the sperm that were frozen in BC diluent exhibited a higher fertility rate (66%, 16/24) compared to the mares that were inseminated with the sperm that were frozen in BCLS20 (40%, 10/25; Pc 0.05). Finally, in a third trial, the sperm that were frozen in BC resulted in a higher fertility rate in mares (75%, 18/24) compared to the sperm that were frozen in BCLS10 (41%, 10/24; P < 0.05). Although replacing the egg yolk in the BC cryodiluent with soybean lecithin provided similar laboratory results for stallion sperm, after cryopreservation, the sperm that was frozen with soybean lecithin in the diluent correlated with lower fertility rates. Based on these results, we concluded that the use of BCLS can be used as an alternative diluent for cryopreserving stallion sperm. However, the resulting reduced fertility rate is a matter of concern. Further studies are necessary to clarify the reasons for this decrease in fertility and to determine the optimal lecithin concentration for diluents to freeze stallion sperm. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Equine; Freezing semen; Egg yolk; Soybean lecithin; Fertility